RISK FACTORS FOR THE OCCURRENCE OF COVID-19 IN PEOPLE WITH TYPE 2 DIABETES MELITUS IN THE COMMUNITY RT 006/002 TELUK JAYA, VILLAGE JAYA, DISTRICT IN 2022 - Sapitri; Dinda Nur Fajri Hidayati Bunga; Hilda Meiryandah Agil (Jurnal Medicare, 2023)
Background: Based on data from the International Diabetes Federation 2020, the number of diabetics continues to increase in various countries, including Indonesia. The prevalence of diabetes in Indonesia still reaches 6.2 percent with 10,681,400 cases. Diabetes Melitus (DM) is a metabolic disorder disease that affects the work of insulin in glucose absorption. Factors related to the occurrence of COVID-19 in a person with type 2 diabetes Melitus include characteristics consisting of gender, age and Activity Of Daily Living as well as foods that can increase high levels of sugar in the body, this is reviewed from the results of other studies conducted by Smith (2021) in the journal (Apin, 2021). Research Objectives: This study has a general objective, namely to determine the Risk Factors for the Occurrence of Covid-19 in People with Type 2 Diabetes Melitus in the RT community. 006/002 Teluk Jaya Village, Jaya District, in 2022. Research Method: The design in this study uses Observational Analytics with a Cross Sectional research design, the sampling technique used in this study is a total sampling with a total sample of 50 respondents in accordance with the inclusion criteria, measured using a digital questionnaire and carried out statistical tests using Chi Square. Results: Based on the results of the chi square statistical test output obtained.. It can be concluded that the Value of Asymp Significance (0.000) < the value of α (0.05), this indicates that H0 is rejected. Thus, it can be concluded that there is a relationship between ADL and the confirmation of COVID-19 in the COMMUNITY RT006/002 Teluk Jaya Village, Jaya District, Karawang Regency. Conclusion: Risk Factors for the Occurrence of Covid-19 in People with Type 2 Diabetes Melitus in the RT community. 006/002 Teluk Jaya Village, Jaya District, in 2022.